Growing environments and cultivar selection limits wheat growth and yield potential in Punjab - Singh, J; Biswas, B; Dhaliwal, L K (Plant Science Today, 2025)
Selecting a suitable sowing time and cultivar can play a pivotal role in sustaining wheat productivity in north India while mitigating the influence of climate extremes. Field experiments were conducted in two distinct climatic regions (Ludhiana and Gurdaspur), of Punjab, India to assess the influence of different sowing environments and cultivars on wheat growth and yield. The crop was sown on three dates (early-5 November, mid-20 November and late-5 December) with two popularly grown wheat cultivars (PBW725 and PBW677). The results indicated that mid and late sowing significantly shortened phenological phases compared to early sowing at both study sites. Wheat sown on 5 November accumulated more thermal time, exhibited a greater leaf area index (LAI), intercepted more photosynthetically active radiation (IPAR), and demonstrated superior radiation use efficiency (RUE). Early-sown wheat also produced higher biological yield (BY), grain yield (GY), irrigation water use efficiency and heat use efficiency compared to delayed sowing at both sites. The wheat cultivar PBW725 outperformed PBW677 in terms of phenological duration, yield, thermal time accumulation, IPAR, LAI and RUE at both sites. IPAR and RUE exhibited a strong positive correlation and regression with the periodic dry matter accumulation of wheat. Linear regression revealed that LAImax (maximum LAI) and ?LAI (accumulated LAI) were the best determinants of BY of wheat. These findings highlight the significance of optimizing growing environments and cultivar selection in mitigating climate extremes and sustaining wheat production in the diverse agro-climatic conditions of Punjab.